(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Student assessments are the traditional methods of assessing academic success, and they areconsidered to affect one’s career. This study evaluated the levels of salivary stress biomarkers represented bycortisol and total salivary protein during final academic assessments of dental undergraduates.Methods: Saliva samples were obtained, one before the exam another afterwards. Concentrations of salivarystress biomarkers were obtained by enzyme-linked immunosorbent assay (ELISA).Results: Before the exam, the two parameters were dramatically higher than afterwards, with a substantialdifference between the levels of salivary protein and cortisol (p=0.000, 0.000 consecutively).Conclusion: Stress induced by academic examinations may increase the level of salivary stress biomarkersin the short term.